A WEB-BASED STEGANOGRAPHY FRAMEWORK USING DISCRETE COSINE TRANSFORM FOR SECURE STUDENT DATA MANAGEMENT - Awang Pradana; Nur Sartina (STKIP PGRI Tulungagung, 2025)
The objective of the research was to implement the method of secure data storage through the use of steganography techniques using the Discrete Cosine Transform (DCT) method. The impetus for the research is the increasing threat to the security and confidentiality of student data, such as unauthorized file deletion, data theft, unauthorized data use, and data utilization for unintended purposes. The research applied the ADDIE Research and Development (RD) model, which consists of the following five stages: Analysis, Design, Development, Implementation, and Evaluation. The system uses a modified DCT coefficient at position (2,1) with thresholds of 12.0 for embedding and 6.0 for extraction on 8×8 pixel blocks, following IEEE standards. The dataset comprised 14 images corresponding to various personal data files of Computer Engineering students, such as family cards, ID cards, and birth certificates. The system was implemented using the Laravel framework integrated with Python scripts for DCT algorithm processing. Experimental and questionnaire-based testing with 14 respondents demonstrated that the system achieves high imperceptibility, with an average MSE of 2.847 and PSNR of 46.89 dB. The system achieved an average embedding time of 67.8 ± 54.2 seconds and extraction time of 34.2 ± 22.8 seconds, with throughput rates of 1.068 kbit/s for embedding and 1.908 kbit/s for extraction. The overall extraction success rate reached 50%, with 100% success for